2017
DOI: 10.1007/s10552-017-0907-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of varied compliance to lung cancer screening recommendations using a microsimulation model

Abstract: Background The US preventive services task force (USPSTF) recently recommended that individuals aged 55–80 with heavy smoking history be annually screened by low-dose computed tomography (LDCT), thereby extending the stopping age from 74 to 80 compared to the national lung screening trial (NLST) entry criterion. This decision was made partly with model-based analyses from cancer intervention and surveillance modeling network (CISNET), which assumed perfect compliance to screening. Methods As part of CISNET, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
(27 reference statements)
1
28
0
Order By: Relevance
“…Similar stage I lung cancer detection (58%), reduced lung cancer mortality (25% at 10 years), and adherence to screening (90%) were recently reported in another large study [4]. Microsimulation modeling predicts a halving of screening benefit when annual screening adherence falls below 50% [8]. Similarly, stage shift from late-to earlystage disease is reduced as the screening interval is increased [9].…”
Section: Introductionsupporting
confidence: 70%
“…Similar stage I lung cancer detection (58%), reduced lung cancer mortality (25% at 10 years), and adherence to screening (90%) were recently reported in another large study [4]. Microsimulation modeling predicts a halving of screening benefit when annual screening adherence falls below 50% [8]. Similarly, stage shift from late-to earlystage disease is reduced as the screening interval is increased [9].…”
Section: Introductionsupporting
confidence: 70%
“…Several studies have shown that patient compliance plays a special role in the successful implementation of mHealth initiatives [ 19 ]. Clinical experience in oncology shows patient compliance to be worse in subgroups with lifestyle-related risk factors (eg, heavy smoking and alcohol abuse), potentially making such patients less eligible for mHealth-based support [ 20 , 21 ]. However, evidence exists that offering mHealth support in addition to close clinical surveillance may improve patient compliance, particularly in the abovementioned subgroups, by providing regular prompts and reminders and facilitating adherence to prescribed exercises or supportive regimens [ 22 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 8 , 9 However, for LCS to achieve similar long-term effectiveness in real-world practice, successful completion of multiple steps, including individuals returning for annual LDCT screening, is vital. 10 …”
Section: Introductionmentioning
confidence: 99%